Development of a novel fermented snack food having α-glucosidase, angiotensin converting enzyme inhibitory and other functional properties - Mukherjee, Arkadeep (My University, 2013)
This study aimed to develop a fermented snack food having α-glucosidase and Angiotensin Converting Enzyme (ACE) inhibiting bioactive substances along with other functional properties. First, the snack food which comprised of a mixture of flour of Vigna mungo and chickpea were made into a batter, fermented with a Lactococcus lactis strain (previously characterized in the laboratory for probiotic attributes) and then steamed. Extract concentration of 200 mg/ml exhibited 13.88 ± 0.36 % inhibition of α-glucosidase having IC50 value of 3.804 mg/ml of the total peptide which is almost 21 times increase in the percent inhibition with respect to control which was prepared without addition of the strain. Inhibition of ACE was about six folds from the control exhibiting 26.85 ± 1.166 %. Sensorial analysis based on 9 point hedonic scale scored adequately for general acceptability both for adults and elderly. Both sensory and nutraceuticals produced were retained over 48 hours at 4°C. The results of this study suggest a potential of applicability of this functional snack food for both adults and the elderly. However stability of these peptides in acidic environment (gut) and clinical studies are of utmost importance prior to application of this functional food.
Master of Science-Microbiology, Dissertation
Keywords: α-glucosidase; Lactococcus lactis; Angiotensin Converting Enzyme